2018
DOI: 10.3390/molecules23112821
|View full text |Cite
|
Sign up to set email alerts
|

Genuine and Sequestered Natural Products from the Genus Orobanche (Orobanchaceae, Lamiales)

Abstract: The present review gives an overview about natural products from the holoparasitic genus Orobanche (Orobanchaceae). We cover both genuine natural products as well as compounds sequestered by Orobanche taxa from their host plants. However, the distinction between these two categories is not always easy. In cases where the respective authors had not indicated the opposite, all compounds detected in Orobanche taxa were regarded as genuine Orobanche natural products. From the about 200 species of Orobanche s.l. (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 77 publications
0
10
0
1
Order By: Relevance
“…Only a small part of holoparasitic species from Orobanchaceae in the world have been studied for their phytochemical properties. Despite this, they were found to have many biological and therapeutic effects (Scharenberg and Zidorn, 2018). PhG species have pharmacodynamic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a small part of holoparasitic species from Orobanchaceae in the world have been studied for their phytochemical properties. Despite this, they were found to have many biological and therapeutic effects (Scharenberg and Zidorn, 2018). PhG species have pharmacodynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, 70 natural products have been described in the Orobanche (among 200 species, ca. 30 species have undergone phytochemical analysis) and Phelipanche genera of the Orobanchaceae family and 19 natural products have been sequestered from the host (Scharenberg and Zidorn, 2018). The Polish team studied six species belonging to the genera Orobanche and Phelipanche and reported that they are rich in PhGs and their number is greater than in Herba Cistanches.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, natural products and their derivatives have attracted great deal of interest as a source for the development of new diverse bioactive compounds due to their high safety profile and cost effectiveness [20,21,22,23,24,25,26]. Among them, pentacyclic triterpenes are the subjects of numerous studies carried out by chemists engaged in organic synthesis and pharmacology.…”
Section: Introductionmentioning
confidence: 99%
“…Abbes et al, (2014) also investigated the antioxidant activity of methanolic and aqueous extract of Orobanche and revealed that Orobanche might be a potential resource of antioxidant and antibacterial activity. Moreover, Scharenberg et al, (2018) described bioactivities for Orobanche extracts and natural products isolated from Orobanche species and showed it has antioxidative and antiinflammatory effects analgesic, antifungal and antibacterial activities. Therefore, in the present study, an effort has been made to establish the scientific validity for the ameliorating…”
Section: Introductionmentioning
confidence: 99%